2013
DOI: 10.1177/1010539513498768
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Leptospirosis Infection in Humans and Implications for Public Health Intervention in Indonesia and the Asia-Pacific Region

Abstract: Prevention and control of leptospirosis require an understanding of risk factors. This review identifies risk factors associated with leptospirosis infection from countries in the Asia-Pacific region, and compares and contrasts these data with those available from Indonesia. MEDLINE, PubMed, and Scopus databases were used to search for relevant articles. Indonesian gray literature was searched for leptospirosis risk factor studies in Indonesia. A total of 34 articles were included in this review. The contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 26 publications
4
42
1
2
Order By: Relevance
“…However, a systematic review of leptospirosis in Indonesia stated that eight out of 13 Indonesian studies and about a quarter of studies from other Asia-Pacific countries had reported a significant association between the existence of rats near human habitation and the occurrence of human leptospirosis infection or disease. Surprisingly, none of the 11 Indonesian studies showed a significant association between the existence of domestic animals/livestock close to residential premises and leptospirosis infection [11].…”
Section: The Presence Of Rodent and History Of Contactmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a systematic review of leptospirosis in Indonesia stated that eight out of 13 Indonesian studies and about a quarter of studies from other Asia-Pacific countries had reported a significant association between the existence of rats near human habitation and the occurrence of human leptospirosis infection or disease. Surprisingly, none of the 11 Indonesian studies showed a significant association between the existence of domestic animals/livestock close to residential premises and leptospirosis infection [11].…”
Section: The Presence Of Rodent and History Of Contactmentioning
confidence: 99%
“…Research in Marseille France in 2011 also concluded that the cause of leptospirosis was a pile of garbage inviting the presence of rodents [20]. Indonesian studies frequently (13; 92.9%) point to flooding, stagnant water surrounding the house, poor sewer condition, and poor sanitation of the house and surroundings as potential environmental risk or modifiable determinants for leptospirosis infection [11]. In developing countries, high infection rates were also found in cities, essentially within disadvantaged urban areas that usually show poor sanitation and where rodents are numerous [6,26,[32][33][34].…”
Section: Environment Condition and The Presence Of Pet As Potential Rmentioning
confidence: 99%
See 1 more Smart Citation
“…Eutrophication and degraded aquatic ecosystem are pervasive issues concerning urban rivers in Yogyakarta. Waterborne and water-deprived diseases (such as diarrhea, dysentery, skin infections and conjunctivitis) and water-related diseases, such as rodent-borne leptospirosis (Sakundarno et al, 2014) are endemic in neighborhoods of the river basins. Due to poorly constructed houses built along the river flood plains, pneumonia and tuberculosis, associated with overcrowding, poor ventilation and lack of natural light, are more frequently encountered.…”
Section: Introductionmentioning
confidence: 99%
“…En Japón KOIZUMI et al, (2009) aisló cepas de Leptospira de ratas urbanas y afirman que estas continúan siendo importantes reservorios de leptospirosis en zonas urbanas. (SAKUNDARNO et al, 2014). En Indonesia y otros países de Asia y del Pacífico determinaron como factores de riesgo para infección por leptospirosis la presencia de ratas y actividades relacionadas con el contacto con el agua superficial contaminada (SAKUNDARNO et al, 2014) Títulos del serovar Grippothyphosa, se ha asociado con mapaches, marsupiales y bovinos (FERRO et al, 2006); los serovares Icterohaemorrhagiae y Copenhageni, con ratas, y el serovar Pomona, con ganado porcino y bovino (BARTHI et al, 2003;LEVETT, 2001).…”
Section: Resultados Y Discusiónunclassified